Validation of patients’ satisfaction regarding medications’ information questionnaire (Psmiq) in Karachi, Pakistan - Rahim, Najia; Muhammad, Iyad Naeem; Shakeel, Sadia; Iffat, Wajiha; Maboos, Madiha; Jamshed, Shazia Qasim (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2017)
SUMMARY. The aim of present study was to develop a validated patient satisfaction regarding medications’ information questionnaire (PSMIQ). It was an extra cultural adaptation of previous questionnaires used in other part of the world. The PSMIQ was premeditated by an expert group of 15 physicians and 15 pharmacists from a formerly validated questionnaire. A preliminary draft of PSMIQ comprised of seventeen items, with responses recorded on a five Likert scale. The internal validation of PSMIQ was approved by conducting a cross-sectional and analytical study. Around one thousand and fifty patients participated in present study. The validity of PSMIQ items was determined through factor analysis, and the reliability was evaluated with Cronbach’s alpha coefficient (α). Cronbach alpha value for transformed 13-item questionnaire was found to be 0.738. These items were assigned four sub scales. When compared it was observed that these subscales were significantly correlated with one another (p < 0.01). Patient satisfaction level for items regarding general information and usage instructions was above 70% however their satisfaction regarding potential problems and cost issues was less than 40%. Their satisfaction was positively associated with females for subscale 1 and 4 (p < 0.01). Responders who were stable had better total satisfaction scores compared with unstable ones in response to subscale 1, 2 and 3. In response to item regarding potential problematic issue, hypertension patients were 1.687 times more satisfied than patients suffering from other diseases (OR = 1.687; 95% CI = 1.247-2.283). Patient satisfaction survey used in the present study was found to be reliable and valid. Respondents were more satisfied regarding medications’ general information and usage instructions, however not satisfied with information regarding potential problems and cost issues.